KONSEP PENDIDIKAN KARAKTER BERBASIS KEADILAN JENDER - Suriadi Suriadi (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) IAIN Pontianak, 2018)
The Education of Character is an education to build one’s personality through morale education. Character Education has been designed and will be applied in Indonesia, create a great opportunity to minimize even degrade the gender biased factors in Education. Nevertheless, how Indonesian could control and give positive supports to policy maker in Indonesia. By this way, perhaps there is no gender biased, especially in Education.